Change in EEG-EMG synchronization reflecting abnormal functional corticomuscular coupling following stroke: A pilot study - Xiaoling Chen; Jinyuan Zhang; Yingying Hao; Ying Liu; Yinan Yang; Ping Xie (Medicine in Novel Technology and Devices)
Stroke is a common clinical cardiovascular and cerebrovascular disease, which can cause severe motor dysfunction. Therefore, it is an important topic to investigate the abnormality mechanism of the cerebral cortex and the corresponding muscles after stroke. In this study, we investigated the functional corticomuscular coupling (FCMC) at specific frequencies by analyzing differences between stroke patients and healthy controls in hand movements. The transfer spectral entropy (TSE) method was used to analyze simultaneous electroencephalography (EEG) and electromyography (EMG) in the right-hand steady state force task. The results illustrated that healthy subjects had the highest TSE values at the beta band in the EMG→EEG and EEG→EMG directions, and the TSE value in the EEG→EMG direction was higher than that in the EMG→EEG direction. In contrast, for stroke patients, beta band coupling was weakened, and there was a notably higher enhancement of alpha and gamma bands in the EMG→EEG direction relative to the EEG→EMG direction. Further analysis found significant correlations between TSE area values at beta2 and gamma2 bands and clinical rating scales. This study demonstrates the frequency specificity properties of FCMC estimated by TSE can assess the rehabilitation status of stroke patients and contribute to our comprehension of the potential mechanism of motor control systems.